BIOECONOMY AND BIOECONOMICS: ARE THEY THE SAME THING? (International Journal of Innovative Technologies in Economy, 2021)
Numerous studies in academic literature study bioeconomy as part of the worldwide desire to find new or more sustainable ways to obtain economic and cultural growth. They view it as a new economic sector used to invent, promote and develop processes compatible with a durable environment. Bioeconomics has had a constant development in scientific literature in the last two centuries. It was created to link to powerful sciences: biology and economics, in an endeavor to broaden the existing theories in both disciplines or create new ones. The connection was created two-fold: using economic concepts and models to analyze biological phenomena or using a biological perspective to study economic behavior. This paper endeavors to present a brief overview of the different approaches found in literature concerning the concepts of “bioeconomy” and "bioeconomics", their similarities, differences and areas or overlap.